MODEL QUANTUM LEARNING BERBASIS NEAR POD UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISTEM PENCERNAAN SISWA DIGITAL NATIVE ERA SOCIETY 5.0 - Anjarwati, Ani; Siti Qomariyah, Ryzca; Fatimattus Az Zahra, Putri (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
As an educators, it is important to apply the learning principles of motivation, attention, activity, and feedback to ensure successful learning. However, in reality there are various obstacles that prevent students from achieving high learning outcomes. This happens to class VD students at Gloria 3 Christian Elementary School, Surabaya, where they often experience learning difficulties, especially in the subject "Human Digestive System" in science class. There is a quantum learning model that aims to overcome student boredom at school. The quantum learning model emphasizes that the role of learning media in the form of songs has advantages in increasing the effectiveness of elementary school students' education. Based on the learning results obtained in Cycle I and Cycle II, the highest score for students in Cycle I was 100 points, the lowest score was 20 points, and the average was 66.8 points. In Cycle II the highest score was 100, the lowest score was 50, and the average was 82.8. Therefore, it appears that the use of singing media has a positive influence on fifth grade students achieving better learning outcomes with material related to the human digestive system. The human digestive system is received positively by students.